Pengaruh Belanja Modal, Pendapatan Asli Daerah Dan Dana Alokasi Umum Terhadap Kinerja Keuangan Dengan Pengawasan Sebagai Variabel Moderating Di Kabupaten/Kota Provinsi Riau Tahun 2014 - 2018 - Nora Angelina; Yulia Efni; Muhammad Rasuli (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2020)
This study aims to see and the effect of capital expenditure, local revenue and general allocation funds on financial performance with supervision as a moderating variable in regencies / cities of Riau Province in 2014-2018. The population in this study is the regional financial performance in Riau Province as much as 12 (twelve) Districts / Cities during 2014 - 2018. The sampling method used the census method or saturated samples, namely the entire population became the research sample so that the total sample used in this study was 60. The results in this study are that capital expenditures, local revenue and general allocation funds have a significant positive effect on regional financial performance. Supervision has a significant positive effect on financial performance. Supervision can moderate between capital expenditures, local revenue and general allocation funds and regional financial performance.